2020
DOI: 10.3390/microorganisms8081144
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hydrogen Cyanide to the Antagonistic Activity of Pseudomonas Strains Against Phytophthora infestans

Abstract: Plants face many biotic and abiotic challenges in nature; one of them is attack by disease-causing microbes. Phytophthora infestans, the causal agent of late blight is one of the most prominent pathogens of the potato responsible for multi-billion-dollar losses every year. We have previously reported that potato-associated Pseudomonas strains inhibited P. infestans at various developmental stages. A comparative genomics approach identified several factors putatively involved in this anti-oomycete activity, amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 34 publications
(44 reference statements)
2
26
0
Order By: Relevance
“… 14 , 22 . Anand et al 23 reported reducing P. infestance mycelial growth by BCA producing HCN. The exact mechanism of how HCN reduces the growth is not yet confirmed.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 22 . Anand et al 23 reported reducing P. infestance mycelial growth by BCA producing HCN. The exact mechanism of how HCN reduces the growth is not yet confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…At the transition phase between exponential and stationary growth, the experiment was stopped, the OD600 was measured using Cytation5 automated plate reader and NaOH was collected. In a 96-well plate aliquots of 100 μl of collected NaOH sample were mixed with 100 μl of 1 M HCl (Fisher Scientific U.K. Ltd) and immediately covered with HCN detection filter paper 13 . After 30 min incubation at room temperature, the filter paper was scanned using Epson Perfection V370 Photo scanner and analysed using ImageJ image analysis software.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we observed that the mutants had gained additional antimicrobial capacities, e.g. inducing higher inhibition of the pathogen's zoospore germination 13 . This prompted us to quantify the mutants' secretion of siderophores, as these iron-chelators are well-known mediators of antifungal activity 14 .…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, polyfunctional biologics application improves the crop quality contributing to carbohydrates, proteins, vitamins, macro- and microelements accumulation in agricultural products [ 53 , 54 , 55 ]. In particular, this applies to the quantitative and qualitative indicators of the potato harvest [ 56 , 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%